The permanence of women in abusive relationships in the light of Schema Therapy (Research, Society and Development, 2022)
Gender studies in Brazil, especially with regard to violence, are dedicated for the most part to examining the etiologies of domestic violence, especially from physical aggression, as well as its effects. In this perspective, this study is dedicated to discussing not only physical damage, but mainly the motivations that lead women to remain in abusive relationships, their knowledge about what an abusive relationship is, in addition to understanding the harm that violence causes. psychological health brings women's mental health. The collected sample consisted of 5 participants, composed entirely of women, from which semi-structured interviews were carried out through Google Meet. The inclusion criteria considered were being a woman, being in a stable relationship for at least one year, being 18 years of age or older, having signed the Free and Informed Consent Form (in the virtual modality), as well as accepting to participate in the study.